1200 years of decadal-scale variability of Mediterranean vegetation and climate at Pantelleria Island, Italy - Calò, Camilla; Henne, Paul D.; Eugster, Patricia; van Leeuwen, Jacqueline; Gilli, Adrian; Hamann, Yvonne; La Mantia, Tommaso; Pasta, Salvatore; Vescovi, Elisa; Tinner, Willy (HOLOCENE, 2013)
A new sedimentary sequence from Lago di Venere on Pantelleria Island, located in the Strait of Sicily between Tunisia and Sicily was recovered. The lake is located in the coastal infra-Mediterranean vegetation belt at 2 m a.s.l. Pollen, charcoal and sedimentological analyses are used to explore linkages among vegetation, fire and climate at a decadal scale over the past 1200 years. A dry period from ad 800 to 1000 that corresponds to the Medieval Warm Period' (WMP) is inferred from sedimentological analysis. The high content of carbonate recorded in this period suggests a dry phase, when the ratio of evaporation/precipitation was high. During this period the island was dominated by thermophilous and drought-tolerant taxa, such as Quercus ilex, Olea, Pistacia and Juniperus. A marked shift in the sediment properties is recorded at ad 1000, when carbonate content became very low suggesting wetter conditions until ad 1850-1900. Broadly, this period coincides with the Little Ice Age' (LIA), which was characterized by wetter and colder conditions in Europe. During this time rather mesic conifers (i.e. Pinus pinaster), shrubs and herbs (e.g. Erica arborea and Selaginella denticulata) expanded, whereas more drought-adapted species (e.g. Q. ilex) declined. Charcoal data suggest enhanced fire activity during the LIA probably as a consequence of anthropogenic burning and/or more flammable fuel (e.g. resinous Pinus biomass). The last century was characterized by a shift to high carbonate content, indicating a change towards drier conditions, and re-expansion of Q. ilex and Olea. The post-LIA warming is in agreement with historical documents and meteorological time series. Vegetation dynamics were co-determined by agricultural activities on the island. Anthropogenic indicators (e.g. Cerealia-type, Sporormiella) reveal the importance of crops and grazing on the island. Our pollen data suggest that extensive logging caused the local extinction of deciduous Quercus pubescens around ad1750.
The following values have no corresponding Zotero field: pub-location: 1 OLIVERS YARD, 55 CITY ROAD, LONDON EC1Y 1SP, ENGLAND publisher: SAGE PUBLICATIONS LTD
Keywords: '"Little Ice Age' (LIA); 'Medieval Warm Period' (MWP); central Mediterranean; Fire history; Pinus pinaster; Quercus ilex; Quercus pubescens; vegetation history

Spatial pattern of soil compaction: Trees’ footprint on soil physical properties - Alameda, David; Villar, Rafael; Iriondo, José M. (Forest Ecology and Management, 2012)
Soil compaction, a determinant of forest regeneration and ecosystem functioning (e.g., biomass production), can show an aggregated spatial pattern which can be shaped by the effect of tree canopy. This work studies the inﬂuence of tree canopy type (Quercus ilex subsp. ballota, and Pinus pinaster) on the spatial distribution of variables related to soil compaction in a Mediterranean forest in southern Spain. The spatial structure of this plant-soil interaction was analyzed using the spatial analysis by distance indices methodology (SADIE). Our results showed that variables related to soil compaction, such as bulk density, penetration resistance, water content and organic matter, showed an aggregated spatial pattern which was associated to the species’ tree canopy and presence of open sites. Thus, high organic matter content and low bulk density were found under the Quercus canopy, whereas the contrary was observed under the Pinus canopy. Open sites showed similar soil properties to those than under the Pinus canopy. Soil compaction pattern and tree canopy had a clear effect on herbaceous production. In two consecutive years (2007 and 2008), herbaceous production was higher under the Quercus canopy than under the Pinus canopy. Mean values of herbaceous production in open sites were similar to those under the Quercus canopy, and no spatial association was found between open sites and herbaceous production. Structural equation modeling (SEM) was used to describe the causal relationships between tree canopy types, soil compaction related variables and herbaceous production. Results showed that tree canopy affects soil compaction variables and its effects on herbaceous production are mainly produced by a positive effect of organic matter (at 2–7 cm depth) and a negative effect of penetration resistance (at 9–14 cm depth). Therefore, forest management should consider that the replacement of one species for another or changes in tree density are likely to have important consequences in soil compaction and ecosystem functioning.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Bulk density; Herbaceous production; organic matter; Penetration resistance; Pinus pinaster; Quercus ilex

Assessment of mycorrhizal colonisation and soil nutrients in unmanaged fire-impacted soils from two target restoration sites - Dias, J. M.; Oliveira, R. S.; Franco, A. R.; Ritz, K.; Nunan, N.; Castro, P. M. L. (Spanish Journal of Agricultural Research, 2010)
The mycorrhizal colonisation of plants grown in unmanaged soils from two restoration sites with a fire history in Northern Portugal was evaluated from the perspective of supporting restoration programmes. To promote restoration of original tree stands, Quercus ilex L. and Pinus pinaster Ait. were used as target species on two sites, denoted Site 1 and 2 respectively. The aim of the study was to assess whether mycorrhizal propagules that survived fire episodes could serve as in situ inoculum sources, and to analyse the spatial distribution of soil nutrients and mycorrhizal parameters. In a laboratory bioassay, P. pinaster and Q. ilex seedlings were grown on soils from the target sites and root colonisation by ectomycorrhizal (ECM) and arbuscular mycorrhizal (AM) fungi was determined. The ECM root colonisation levels found indicated that soil from Site 2 contained sufficient ECM propagules to serve as a primary source of inoculum for P. pinaster. The low levels of ECM and AM colonisation obtained on the roots of plants grown in soil from Site 1 indicated that the existing mycorrhizal propagules might be insufficient for effective root colonisation of Q. ilex. Different ECM morphotypes were found in plants grown in soil from the two sites. At Site 2 mycorrhizal parameters were found to be spatially structured, with signif icant differences in ECM colonisation and soil P concentrations between regions of either side of an existing watercourse. The spatial distribution of mycorrhizal propagules was related to edaphic parameters (total C and extractable P), and correlations between soil nutrients and mycorrhizal parameters were found.
Keywords: arbuscular mycorrhiza; ectomycorrhiza; Pinus pinaster; post fire; Quercus ilex; soil restoration; spatial variation

Breeding performance of the Blue Tit Parus caeruleus in a patchy Mediterranean landscape - Catalan, R M; Haeger, J F (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1999)
This study compares reproductive strategy and breeding success of Parus caeruleus in a helm-oak (Quercus rotundifolia) forest and a pine plantation (Pinus pinea and P. pinaster) in the southern Iberian Peninsula. During the breeding period, an asymmetric flow of individuals takes place from the helm-oak forest to the pine plantation. This flow is favoured by nestboxes where Blue tits can lay their eggs. During the winter, a large part of the population moves back from the pine plantation to the helm-oak forest. Breeding pair density was much higher in the helm-oak forest than in the pine plantation. This may bt accounted for by the poorer quality of the resources available in the pine plantation which birds try to compensate for with larger breeding territories. Breeding density and most life-history traits examined (timing of breeding, clutch site, egg size, number of fledglings and fledgling weight) were similar in both habitats, as a result of the phenotypic plasticity of this species. Although breeding success was similar in both habitats, recruitment of new individuals per unit area was higher in the helm-oak forest. The consequences of pine plantations, as a form of forestry management, on species conservation is discussed.
APS
Keywords: breeding success; Holm oak; iberian peninsula; Parus caeruleus; Pinus pinaster; Pinus pinea; Quercus ilex; reproductive strategies

Influence of leaf litter type on the chemical evolution of a soil parent material (sandstone) - Madeira, M; Ribeiro, C (Biogeochemistry, 1995)
The influence of leaves of Quercus suber L. and Eucalyptus globulus Labill. and needles of Pinuspinaster Ait. on a sandstone substrate was assessed through lysimetric studies during a ten-year period at a site in Central Portugal. The decomposition rate of Q. suber leaf litter was similar to that of E. globulus and higher than that of P pinaster needle litter. The proportion of nitrogen released from the Q. suber leaf litter was higher than that lost from the other organic species. Such a release was proportional to the initial nitrogen content in the substrates. The concentrations of both NHa-N and NO3-N were much higher in leachates collected under Q. suber leaf litter than in those collected under the other organic substrates. A similar trend was found in the leachates collected under the mineral substrate influenced by the studied organic substrates. The leachate concentrations of mineral N (especially NOs-N) were higher from the mineral substrate under Q. suber leaf litter than from this organic substrate itself. The mineral substrate under leaf litter of E. globulus or needle litter of P pinaster showed an increase in exchangeable base cations and pH values, and a decrease in extractable Al. Conversely, in the substrate with Q. suber leaf litter there was only a slight increase in exchangeable base cations and pH values, and a decrease in extractable Al. These results combined with those obtained in soils underE. globulus plantations indicate that changes found in these soils are due to soil and forest m
Keywords: decomposition rate; elemental fluxes; EUCALYPTUS; Leaching; leaf litter; Pinus pinaster; Quercus suber; soil chemistry

Germination and regeneration mechanisms in Mediterranean degenerate forests - Bacilieri, R; Bouchet, M A; Bran, D; Grandjanny, M; Maistre, M; Perret, P; Romane, F (Journal of Vegetation Science, 1993)
Abstract. Germination and developmental behaviour during juvenile stages are of importance in relation to succession mechanisms acting on plant communities. This is particularly so in the Mediterranean region, where the climatic summer drought causes stress. We investigated and compared germination and development of four tree species in two parts of the French Mediterranean region where the original dominant tree species (Quercus pubescens) has been largely replaced by Quercus ilex in the southern part, and Castanea sativa in the northern part. Observed differences in germination rates and developmental behaviour, especially shootroot ratio and the role of water supply, suggest that other species may eventually replace the current dominant species.
Keywords: Castanea sativa; Pinus pinaster; Quercus ilex; Quercus pubescens

Germination and regeneration mechanisms in Mediterranean degenerate forests - Bacilieri, R.; Bouchet, M. A.; Bran, D.; Grandjanny, M.; Maistre, M.; Perret, P.; Romane, F. (Journal of Vegetation Science, 1993)
Abstract. Germination and developmental behaviour during juvenile stages are of importance in relation to succession mechanisms acting on plant communities. This is particularly so in the Mediterranean region, where the climatic summer drought causes stress. We investigated and compared germination and development of four tree species in two parts of the French Mediterranean region where the original dominant tree species (Quercus pubescens) has been largely replaced by Quercus ilex in the southern part, and Castanea sativa in the northern part. Observed differences in germination rates and developmental behaviour, especially shootroot ratio and the role of water supply, suggest that other species may eventually replace the current dominant species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Castanea sativa; Pinus pinaster; Quercus ilex; Quercus pubescens